Cluster Monitoring Platform Based On Self Adaptable Probes - Saab, Céline Boutros; Bonnaire, Xavier (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41212, 2000)
Distributed systems based on cluster of workstations are now largely adopted in industries and universities, but they are more complex to manage. Some value added tools offer new services to the operating system to efficiently exploit the cluster power. Usually, such a tool nedds to monitor a set of resources with a variable granularity, and most existing tools use a fixed granularity. In this paper, we propose to use a generic monitoring platform with a variable granularity based on a self adaptable probes, which will offer an automatic granularity tuning to avoid a performance fine grain monitoring,and a reliable mechanism to handle a resource emergency state. Self adaptable monitoring also allows to reduce the overhead produced by the observation system.